Examining The Impact Of Strategic Supplier Partnerships, Customer Relationship, Postponement, And Supply Chain Responsiveness On Operational Performance: The Moderating Effect Of Demand Uncertainty - kevin Letsoin; Wahyuningsih Santosa; Triwulandari SD (Business and Entrepreneurial Review, 2023)
Uncertainty in demand is a common problem that always occurs in various businesses, this is inseparable from market trends that continue to change so that the wants and needs of consumers also change. The role of companies in overcoming demand uncertainties and maintaining firm performance is an issue that is debated among scholars. Therefore, this study investigates the moderating effect of demand uncertainty on the relationship between strategic supplier partnerships-supply chain responsiveness, customer relations-supply chain responsiveness, and postponement -supply chain responsiveness and operational performance in the 7 largest food and beverage companies in the Indonesia, which is in Jakarta. in Jakarta because the researchers come from the Jakarta and know enough about the condition of the development of food and beverage companies in the area which is the research objective. Seven hypotheses were formulated and tested using correlation and regression statistical techniques on data collected from 150 respondents through a questionnaire survey and purposive sampling technique. The findings, strategic supplier partnerships, and customer relationships positively and significantly affect supply chain responsiveness, while delays negatively and significantly affect supply chain responsiveness, and supply chain responsiveness also has a positive and significant impact on operational performance. In addition, demand uncertainty positively moderates the relationship between strategic supplier partnerships and supply chain responsiveness, and positively moderates the relationship between customer relationships and supply chain responsiveness. However, demand uncertainty negatively and significantly moderates the relationship between postponement and supply chain responsiveness. Based on these findings, managers are expected to be able to reduce the effect of demand uncertainty so that operational performance can be improved.